Signaling mechanisms and their regulation during in vivo or in vitro maturation of mammalian oocytes - Patrycja Strączyńska; Krzysztof Papis; Emilia Morawiec; Michał Czerwiński; Zdzisław Gajewski; Anita Olejek; Anna Bednarska-Czerwińska (BMC, 2022)
Abstract In vitro fertilization (IVF) is currently one of the most effective methods of infertility treatment. An alternative to commonly used ovarian hyperstimulation can become extracorporeal maturation of oocytes (in vitro maturation; IVM). Fertilization and normal development of the embryo depends on the cytoplasmic, nuclear and genomic maturity of the oocyte. The microenvironment of the ovarian follicle and maternal signals, which mediate bidirectional communication between granulosa, cumulus and oocyte cells, influence the growth, maturation and acquisition of oocyte development capability. During oogenesis in mammals, the meiosis is inhibited in the oocyte at the prophase I of the meiotic division due to the high cAMP level. This level is maintained by the activity of C-type natriuretic peptide (CNP, NPPC) produced by granulosa cells. The CNP binds to the NPR2 receptor in cumulus cells and is responsible for the production of cyclic guanosine monophosphate (cGMP). The cGMP penetrating into the oocyte through gap junctions inhibits phosphodiesterase 3A (PDE3A), preventing cAMP hydrolysis responsible for low MPF activity. The LH surge during the reproductive cycle reduces the activity of the CNP/NPR2 complex, which results in a decrease in cGMP levels in cumulus cells and consequently in the oocyte. Reduced cGMP concentration unblocks the hydrolytic activity of PDE3A, which decreases cAMP level inside the oocyte. This leads to the activation of MPF and resumption of meiosis. The latest IVM methods called SPOM, NFSOM or CAPA IVM consist of two steps: prematuration and maturation itself. Taking into account the role of cAMP in inhibiting and then unblocking the maturation of oocytes, they have led to a significant progress in terms of the percentage of mature oocytes in vitro and the proportion of properly developed embryos in both animals and humans.